Ganoderma lingzhi culture enhance growth performance via improvement of antioxidant activity and gut probiotic proliferation in Sanhuang broilers - Liu, Xuzhou; Huang, Liling; Shi, Yan; Wang, Xiaoguo; Luo, Yanglan; Wei, Shiyan; Qin, Yanchun; Lu, Yuwen; Zhang, Wenlong; Ju, Ying; Yan, Yong; Liao, Yuying (Frontiers in Veterinary Science, 2023)
The experiment was conducted to evaluate the effects of Ganoderma lingzhi culture (GLC) as a fermented feed on growth performance, serum biochemical profile, meat quality, and intestinal morphology and microbiota in Sanhuang broilers. In addition, the association between gut bacteria and metabolites was investigated via untargeted metabolomic analysis. A total of 192 Sanhuang broilers (112 days old) with an initial body weight of 1.62 ± 0.19 kg were randomly allocated to 4 treatments, 6 replicate pens per treatment with 8 broilers per pen. The 4 treatments contain a control diet (corn-soybean meal basal diet, CON), a positive control diet (basal diet + 75 mg/kg chlortetracycline, PCON), and the experimental diets supplemented with 1.5% and 3% of GLC, respectively. The trial includes phase 1 (day 1 to 28) and phase 2 (day 29 to 56). The results showed that broilers in PCON and GLC-added treatments showed a lower FCR (P<0.05) in phase 2 and overall period and a higher ADG (P<0.05) in phase 2. On day 56, the concentrations of serum SOD (P<0.05), and HDL (P<0.05) and cecal SCFA contents (P<0.05) were increased in broilers fed GLC diets. Broilers fed GLC also showed a higher microbiota diversity and an elevated abundance of SCFA-related bacteria in the caecum. The association between intestinal bacteria and metabolites was investigated via correlation analysis. The differential metabolites in the caecum, such as L-beta-aspartyl-L-aspartic acid and nicotinamide riboside, were identified. In conclusion, dietary GCL supplementation could increase growth performance to some extent. Moreover, GLC might benefit broilers’ health by improving serum HDL content, antioxidant status, SCFAs contents, bacterial diversity, and probiotic proliferation in the caecum.